G169(P) Actup – an interdisciplinary approach to preparing senior paediatric trainees for challenging clinical scenarios. (12th March 2018) - McNaughten, B; Sweeney, R; Murphy, P; Storey, L; Bourke, TW; Thompson, A
Abstract : Aims: In recent years there has been an increasing recognition of the importance of non-technical skills training in medical education. Strong communication and interpersonal skills are crucial to good clinical practice. These are of particular relavence when communicating with team members, parents and patients in challenging situations. We identified a lack of postgraduate training opportunities for paediatric trainees to develop these skills. Our aim was to devise an interdisciplinary training opportunity which would enable senior paediatric trainees to develop their communciation skills by undertaking simualted scenarios based on challenging clinical situations. Methods: Level 3 trainees in our deanery were invited to attend the ACT up course. We recruited a diverse faculty consisting of paediatricians, paediatric nurses, social workers and psychologists. In a unique collaboration, we worked closely with drama students from our local universty. The drama students acted in the role of parents for the simulations. The scenarios focused on challenging clinical encounters which may be seen in paediatric practice. These included safeguarding cases, sudden unexpected death of an infant and discussions around withdrawal of care. Feedback was collected through questionnaires and focus groups conducted by the psychology team. Results: Feedback on the course was excellent. All participants found input from a diverse faculty particularly beneficial. Themes identified on analysis of the focus groups included the importance of the drama students in enhancing the fidelity of the simulations, the necessity of further non-technical skills training in paediatric training and the benefits of debrief following challenging clinical encounters. Conclusions: This course provided an opportunity for senior paediatric trainees to develop their communication skills in challenging situations. Initial feedback was excellent. We strive to establish this course as a regular training opportunity for paediatric trainees in our deanery. The course has also been adopted as an essential component of the undergraduate drama module entitled 'Drama, Health and Social Care' now offered in our local university.